Pengaruh Current Ratio, Return on Equity dan Debt to Equity Ratio Terhadap Harga Saham pada Perusahaan Manufaktur Sub Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada Tahun 2014-2023 - Selvia, Mey; Devyanthi Syarif (Economic Reviews Journal, 2024)
With a focus on manufacturing companies in the property and real estate subsector listed on the Indonesia Stock Exchange, the purpose of this study is to ascertain the impact of current ratio, return on equity, and debt to equity ratio on stock prices for the years 2014–2023. This study employs a quantitative methodology that combines a verification and descriptive strategy. The traditional assumption test, multiple linear regression, Pearson correlation coefficient, determination coefficient, and hypothesis testing with partial (t-test) and simultaneous (f-test) tests are among the statistical testing techniques used. Sixty financial reports from businesses in the Manufacturing Companies in the Property and Rail Estate Sub-Sector provided the sample data. Purposive sampling combined with nonprobability sampling is being used. IBM SPSS version 26.0 was the analysis tool used in this investigation. According to the study's findings, stock prices are somewhat influenced by the current ratio, return on equity, and debt to equity ratio. Stock prices are significantly impacted by the study's concurrently obtained current ratio, return on equity, and debt to equity ratio.